Penerapan Metode Forward Chaining untuk Mendiagnosa Penyakit Rambut Rontok Berbasis Android - Irfan Triputra Isyan (CV. Multi Kreasi Media, 2022)
In the midst of the rapid development of information technology, especially artificial intelligence plays a very important role in today's human activities in making decisions by applying artificial intelligence technology. One of them is by implementing an expert system. An expert system is an application of a system in which the system itself is a duplication of knowledge from an expert related to the system. Hair loss can occur only on the scalp or the entire body. These symptoms can be temporary or permanent. Lack of knowledge about this hair loss, then made an android-based hair loss diagnosis application that can be used anywhere and anytime by the user. The making of this hair loss diagnosis application uses the javascript programming language, then SQLite as a local database, android studio as an android application development and the results of diagnostic analysis using the forward chaining algorithm method in the form of symptoms and diseases of hair loss. Testing the system by testing black box and white box by compiling a flow graph. The results of the application of this application are expected to help knowledge about hair loss and identify hair loss diseases.